Dermatology an illustrated colour text - Gawkrodger, D. J.; Ardern-Jones, Michael R. (Elsevier, 2017)
This concise textbook of dermatology is aimed at medical students, those preparing for the MRCP and MRCGP examinations and specialist nurses. The information is presented in a highly accessible format, using double page spreads for each topic.